PENINGKATAN DAYA SAING MINUMAN FUNGSIONAL INSTAN (SARI APEL CELUP DAN SARI POKAK), SEBAGAI PRODUK KHAS AGROWISATA BATU - Elok Zubaidah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
ABSTRACTBatu city is an agrotourism city that has been growth rapidly, both as a tourism area and as the center of small scale industries. Wild eggplant extract drink and apple bag are the new competitive products that produced by SMEs in Batu City since 2011. Apple bag is a practical innovative beverage made from apple, and wild eggplant extract drink is a traditional beverage from East Java that made from spices herbs. The SMEs problem is the low production capacity due to manual packaging process. The packaging process of Apple bag was done by other company that lead to high cost production and need a long time, and the wild eggplant extract drink packaging was done manually. The impact of this problem is delayed of the consumer demand fulfillment. The aim of community services activities is to introduce the new packaging technology including mini shrink tunnel and packaging sealer. The activities had improved production effectiveness around doubled so the SMEs be able to produce its product more efficient and higher productivity.